Imaging in neurodegenerative disorders - Saba, Luca (Oxford University Press, 2014)
This resource covers all the imaging techniques associated with investigations and diagnoses in neurology for neurodegenerative disorders, as well as new methods such as new tracers, biomarker, gene-array profiling, & the potential for applying such techniques clinically. As new imaging modalities have recently emerged as outstanding non-invasive techniques for the study of the neurodegenerative disorders, the resource discusses high resolution, morphological, metabolic and functional analysis, as well as computed tomography, magnetic resonance, nuclear medicine and molecular imaging.